Global resting‐state functional connectivity of neural oscillations in tinnitus with and without hearing loss. Issue 10 (3rd April 2020) - Demopoulos, Carly; Duong, Xuan; Hinkley, Leighton B.; Ranasinghe, Kamalini G.; Mizuiri, Danielle; Garrett, Coleman; Honma, Susanne; Henderson‐Sabes, Jennifer; Findlay, Anne; Racine‐Belkoura, Caroline; Cheung, Steven W.; Nagarajan, Srikantan S.
Abstract: This study examined global resting‐state functional connectivity of neural oscillations in individuals with chronic tinnitus and normal and impaired hearing. We tested the hypothesis that distinct neural oscillatory networks are engaged in tinnitus with and without hearing loss. In both tinnitus groups, with and without hearing loss, we identified multiple frequency band‐dependent regions of increased and decreased global functional connectivity. We also found that the auditory domain of tinnitus severity, assayed by the Tinnitus Functional Index, was associated with global functional connectivity in both auditory and nonauditory regions. These findings provide candidate biomarkers to target and monitor treatments for tinnitus with and without hearing loss.